Cosmogenic 10Be and 26Al exposure ages of glaciations in the Frankland Range, southwest Tasmania reveal a limited MIS-2 ice advance. (1st February 2017) - Kiernan, Kevin; Fink, David; McConnell, Anne
Abstract: New mapping of the glacial geomorphology coupled with 10 Be and 26 Al exposure age dating of moraines on the flanks of the Frankland Range in south west Tasmania indicate that glacier extent during MIS-2 was far smaller than during earlier glaciations with the ice cover being confined to only the uppermost cirques of the range. Moraines further down the range flanks, ∼50–150 m lower in altitude than the MIS-2 dated advance, indicate that glaciers were only slightly larger during earlier glaciations and, depending on the interpretation of their exposure ages, may range from MIS 7 to MIS 12. These older moraines are nested inside the maximum ice limits of an even more ancient and extensive glaciation, defined by degraded valley floor moraines and coalescing glacio-fluvial fans that remain undated but appear no younger than MIS 12. Patterns of glacial erosion and moraine deposition on the Frankland Range suggest that the more recent glaciations were increasingly influenced by the erosional morphology initiated by earlier glaciers. Microclimatic differences resulting from this earlier glacial topography were particularly influential determinants of glaciation during MIS 2. These results are consistent with emerging evidence from studies of other ranges in southwest Tasmania. Highlights: Local LGM (MIS 2) maximum glaciation is at ∼19–21 ka, is of limited extent and smaller than all earlier advances. Minimum exposure ages of successive older moraines range from MIS-5 to MIS-12. No evidence for MIS 3 or MIS 4 glacial deposits. Ancient glacial landscape sculpting altered younger ice advances. Local topography and microclimate controlled glacial extent during marginal conditions.